Comparison of Indirect and Direct Approaches to Identifying an Unfaithful Partner. Issue 3 (3rd April 2023) - Tang, Yabin; Hans, Jason D.; Vowels, Laura M.
Abstract: Infidelity has been operationalized inconsistently across studies, and measurement approaches have been employed that are not ideally suited for addressing the stigmatized and subjective nature of infidelity, thereby limiting the conclusions that can be drawn from this body of literature. In 2016, Thompson and O'Sullivan took a step toward addressing these shortcomings by implementing an indirect measurement approach. We extend their findings using a sample of 465 married and divorced individuals via MTurk. Substantially more participants reported having engaged in infidelity via the indirect approach than the direct approach, and results suggest that—in contrast to findings from direct questioning—similar percentages of men and women engage in self-defined infidelity. Implications for research and clinical practice are provided.